Atividade vasomotora simpática renal e esplâncnica em um modelo de hipertensão por inibição da síntese de óxido nítrico - Zambrano, Lysien Ivania [UNIFESP] (2016)
Systemic hypertension is a multifactorial disease. Among several factors that contributes to the increase in blood pressure, it highlights the deficiency of nitric oxide (NO) and changes in sympathetic vasomotor activity (SNA). The role of NO in the modulation of autonomic function is still controversial in the literature. This work aimed to study the association of sympatoexcitation with inhibition of NO synthesis-induced hypertension. Thus, the present study evaluated the SNA for two different beds, splanchnic and renal (rSNA and sSNA), mean arterial pressure (MAP), heart rate (HR), arterial baroreceptor control for both territories, as well as possible correlations between these parameters and the plasma levels of NO. After eight days of treatment with N-nitro-L-arginine methyl ester (L-NAME - 20mg / kg / day by gavage), a NO sintase inhibitor, obtain 50% increase in MAP, no change in HR, 29% increase in rSNA and 97% sSNA, as well as an increased response to depressing of arterial baroreceptors. Plasma levels of NO were reduced 31% in animals treated with LNAME. Taken altogether, our results demonstrate that inhibition of NO synthesis promotes major hemodynamic changes and autonomic control improvement to different regions innervated by the sympathetic nerves and it is likely that these changes were caused by reduced NO levels both systemically and within brain regions of autonomic control.